The development of simulation model of carrier injection in quantum dot laser system - Nordin, Norbaizura; Radiman, Shahidan (Asian Research Publishing Network (ARPN), 2016)
The development simulation model of quantum dot (QD) laser is performed based upon rate equations for the carriers and photons in energy states. The rate equation is solved by using Matlab, Runge-Kutta method. In this paper shown that by increasing carrier injection to the active medium of laser, switching-on and stability time of the system would decrease while output power at peak and stationary will be increased. Indirect (non-instantaneous) carrier injection into QD is an essential component of our model and it describes the actual situation for QD laser.